Penerapan Enterprise Resource Planning (ERP) untuk Sistem Informasi Pembelian, Persedian dan Penjualan Barang pada Toko EMI GROSIR dan ECERAN - Ricky Akbar; Juliastrioza Juliastrioza (Jurnal Nasional Teknologi dan Sistem Informasi, 2015)
On Emi Store wholesale and retail business processes of purchasing, inventory, and sales are still made in the traditional and manual. This led to some problems, among others, is often an error occurred recording of purchases and sales of goods, calculation of the transaction, as well as the latest information the availability of goods in the warehouse. Therefore, it is necessary the implementation of Enterprise Resource Planning (ERP) system for purchase information, inventory, and sales of goods aimed at overcoming these problems. ERP implementation stage began with the study of introduction. Its activities namely the introduction of the company as a whole with interviews and observation, identifying the business processes of purchasing, inventory, and sales of goods that are currently running and then make a proposal system in terkomputerisasinya, which is described by using the Business Process Model Notation (BPMN), as well as the depiction of a working model of the system to be applied using use case diagrams. The next stage is to conduct a study of the literature of a variety of books and journals to find a foundation theory and related research. Then do the selection of ERP software, configuration and customization of the ERP software modules, as well as the last application and testing. The results of this study indicate that ERP software that have been selected and applied IE applications can address in Odoo Stores Emi wholesale and retail.